Carbachol and Nicotine in Prefrontal Cortex Have Differential Effects on Sleep-Wake States - Parkar, Anjum; Fedrigon, Donald C.; Alam, Farah; Vanini, Giancarlo; Mashour, George A.; Pal, Dinesh (Frontiers in Neuroscience, 2020)
The role of the brainstem cholinergic system in the regulation of sleep-wake states has been studied extensively but relatively little is known about the role of cholinergic mechanisms in prefrontal cortex in the regulation of sleep-wake states. In a recent study, we showed that prefrontal cholinergic stimulation in anesthetized rat can reverse the traits associated with anesthesia and restore a wake-like state, thereby providing evidence for a causal role for prefrontal cholinergic mechanisms in modulating level of arousal. However, the effect of increase in prefrontal cholinergic tone on spontaneous sleep-wake states has yet to be demonstrated. Therefore, in this study, we tested the hypothesis that delivery of cholinergic agonists - carbachol or nicotine - into prefrontal cortex of rat during slow wave sleep would produce behavioral arousal and increase the time spent in wake state. We show that unilateral microinjection (200 nL) of carbachol (1 mM) or nicotine (100 mM) into prefrontal cortex during slow wave sleep decreased the latency to the onset of wake state (p=0.03 for carbachol, p=0.03 for nicotine) and increased the latency to the onset of rapid eye movement sleep (p=0.008 for carbachol, p=0.006 for nicotine). Although the infusion of 1 mM carbachol increased the time spent in wake state (p=0.01) and decreased the time spent in slow wave sleep (p=0.01), infusion of 10 mM or 100 mM nicotine did not produce any statistically significant change in sleep-wake architecture. These data demonstrate a differential role of prefrontal cholinergic receptors in modulating spontaneous sleep-wake states.